2007
DOI: 10.3800/pbr.2.67
|View full text |Cite
|
Sign up to set email alerts
|

First record of an association between a phyllosoma larva and a Prayid siphonophore

Abstract: A scyllarid lobster phyllosoma larva was observed attached to the siphosome of a prayid siphonophore while SCUBA diving in the Canary Islands. The phyllosoma was straddling the siphosome, which was still alive, with one pereiopodal endopodite per siphosomal cormidia and used its pereiopodal exopodites to pull the siphosome through the water. It did not detach, even after repeated disturbances, and it is proposed that the phyllosoma may be using the prayid siphosome as both food and for protection from predator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…When a phyllosoma had a jelly in its grasp, it was almost always attached to the bell and positioned far from the phyllosoma mouthparts, using their 5th pereiopods (Wakabayashi, Sato, Hirai, & Tanaka, ). Behavioral observations have depicted phyllosoma pulling their gelatinous “host” through the water once they have become attached (Ates, Lindsay, & Sekiguchi, ), indicating that the phyllosoma swimming is not eliminated by the attachment to a gelatinous organism, but the attachment could influence swimming speed or response to currents by altering drag or buoyancy. Once phyllosoma vertical behavior and the fluid mechanics surrounding the larvae are more accurately described, dispersal models should incorporate this information to more accurately simulate their movements in response to current changes and the alterations of drag induced by the attachment to gelatinous zooplankton, which may be size‐dependent.…”
Section: Discussionmentioning
confidence: 99%
“…When a phyllosoma had a jelly in its grasp, it was almost always attached to the bell and positioned far from the phyllosoma mouthparts, using their 5th pereiopods (Wakabayashi, Sato, Hirai, & Tanaka, ). Behavioral observations have depicted phyllosoma pulling their gelatinous “host” through the water once they have become attached (Ates, Lindsay, & Sekiguchi, ), indicating that the phyllosoma swimming is not eliminated by the attachment to a gelatinous organism, but the attachment could influence swimming speed or response to currents by altering drag or buoyancy. Once phyllosoma vertical behavior and the fluid mechanics surrounding the larvae are more accurately described, dispersal models should incorporate this information to more accurately simulate their movements in response to current changes and the alterations of drag induced by the attachment to gelatinous zooplankton, which may be size‐dependent.…”
Section: Discussionmentioning
confidence: 99%
“…1992 ) to observe and collect zooplankton, especially fragile gelatinous forms, in many areas of the ocean. These sampling approaches have led to new species discoveries (Haddock et al 2005 ;Lindsay & Miyake 2007 ), and rapid advances in our understanding of deep sea biology and ecology Ates et al 2007 ;Fujioka & Lindsay 2007 ;Kitamura et al 2008a, b ;. In 2006, Dhugal Lindsay (Japan Agency for MarineEarth Science and Technology) led a pilot study to census gelatinous and hard -bodied zooplankton in Sagami Bay (Japan) using diverse sampling technologies, including an autonomous video plankton recorder (AVPR) with a highdefi nition video camera for color imagery.…”
Section: Zooplankton S Amplingmentioning
confidence: 99%
“…Discoveries of novel Cnidaria and Ctenophora species have resulted (Kitamura et al 2005 ;Fuentes & Pag è s 2006 ;Pag è s et al 2006 ;Hosia & Pag è s 2007 ), some requiring the establishment of new higher taxonomic groups (Lindsay & Miyake 2007 ). This work has also allowed comparisons among regional faunas in light of geological history and environmental conditions, and revealed novel relationships among gelatinous plankton and other organisms (Ates et al 2007 ;Pag è s et al 2007 ;Lindsay & Takeuchi 2008 ;Ohtsuka et al 2009 ).…”
Section: Gelatinous Z Ooplanktonmentioning
confidence: 99%
“…Although real interactions between them are still unclear, it is supposed that the riding of phyllosoma on medusae saves swimming energy and helps in avoiding predation (Herrnkind et al 1976). Recently a scyllarid lobster phyllosoma was reported to swim while dragging a prayid siphonophore behind it, suggesting importance as food and/or defense against predation but refuting the idea of energy-saving due to transportation (Ates et al 2007). A recent molecular technique with 18SrDNA has been applied to identification of food items of some species of scyllarid and palinurid phyllosoma larvae, and suggested that these feed on appendicularians, salps and cnidarians (Suzuki et al 2006).…”
Section: Decapodsmentioning
confidence: 99%